Pengaruh budaya asing terhadap kebudayaan lokal: ancaman atau peluang? - Ramadhanti, Alifia Adzania (Maliki Interdisciplinary Journal, 2024)
This article discusses the influence of foreign cultures on local cultures in Indonesia, and how foreign cultures can be either a threat or an opportunity for local culture. Against the backdrop of Indonesia's rich cultural heritage, composed of various ethnic groups and traditions, this article explores how foreign cultures are often perceived to undermine the authenticity of local cultures through economic and technological dominance. Positive impacts of foreign cultures include enhanced local creativity, increased tourism appeal, and the exchange of ideas and knowledge. Negative impacts include the erosion of cultural identity, decline in the use of local languages, and the rise of consumerist and individualistic behaviors. To address these negative impacts, the strategic roles of the government, religious leaders, cultural figures, and families in education and youth development are crucial. This article employs a literature research approach to analyze the positive and negative impacts of foreign cultures and offers solutions to strengthen local cultural resilience.